Kehilangan Karbon dan Oksigen pada Pemanenan Jati (Tectona grandis Linn. f) Unggul Nusantara di Kebun Percobaan Cogreg, Kecamatan Ciseeng, Kabupaten Bogor - Dwi Agus Sasongko; Ken Dara Cita; Abdul Rahman Rusli; Bambang Supriono (Institut Pertanian Bogor, 2023)
This study aims to calculate the amount of carbon lost and the amount of oxygen that can no longer be produced by the Cogreg Experimental Garden (KPC) due to the harvesting of Nusantara Unggul Teak wood (JUN). Carbon stock loss was measured using the allometric equation method based on the SNI 7724:2011. Calculating the loss of oxygen-producing potential used the comparison method of the atomic weights of carbon and oxygen. The results of this study indicate that the harvesting of JUN at KPC causes a loss of potential carbon storage reserves of 215.384 tons/year or equivalent to IDR7.2 bilions; the loss of oxygen-producing potential is 574,359 tons/year or equivalent to IDR2.66 billions. Meanwhile, the results of harvesting JUN wood can only produce a financial value of IDR1,36 billions. Therefore, the financial value of the KPC's environmental services in the form of carbon storage and oxygen production is much greater than the financial value of harvesting JUN's wood. Keywords: carbon loss, Cogreg Experimental Garden, Jati Unggul Nusantara, oxygen loss